2001
DOI: 10.1177/002215540104900208
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Activity and Cellular Localization of Human Semicarbazide-sensitive Amine Oxidase

Abstract: S U M M A R Y Semicarbazide-sensitive amine oxidase (SSAO), widely distributed in highly vascularized mammalian tissues, metabolizes endogenous and xenobiotic aromatic and aliphatic monoamines. To assess whether its physiological role in humans is restricted to oxidation, we used an immunohistochemical approach to examine the cellular localization of SSAO in human peripheral tissues (adrenal gland, duodenum, heart, kidney, lung, liver, pancreas, spleen, thyroid gland, and blood vessels) and also analyzed its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 34 publications
3
31
0
2
Order By: Relevance
“…Thus, following these doses, the peak plasma concentration would span a concentration range that encompasses the in vitro IC 50 for inhibition of rat lung SSAO by LJP 1586. Although mouse lung contains little SSAO activity compared with that detected in rat or human lungs (Andres et al, 2001), mouse aorta contains abundant SSAO activity. SSAO activity in mouse aorta homogenates was measured ex vivo after orally administering the same doses of LJP 1586 as used in the above experiments.…”
Section: Resultsmentioning
confidence: 83%
“…Thus, following these doses, the peak plasma concentration would span a concentration range that encompasses the in vitro IC 50 for inhibition of rat lung SSAO by LJP 1586. Although mouse lung contains little SSAO activity compared with that detected in rat or human lungs (Andres et al, 2001), mouse aorta contains abundant SSAO activity. SSAO activity in mouse aorta homogenates was measured ex vivo after orally administering the same doses of LJP 1586 as used in the above experiments.…”
Section: Resultsmentioning
confidence: 83%
“…It is therefore conceivable that in addition to soluble primary amines, Lox and SSAO may act on amino acids included in matrix proteins. In addition, considering our methodological approach and the size of arterial samples, it is not possible to establish the relationship between SSAO tissue expression and activity, but this has previously investigated in the work of Jaakkola et al (1999) and Andres et al (2001). In this context, further morphological, biochemical, and molecular investigations will be required to determine this relationship and the exact nature of the SSAO substrate(s) in the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…SSAO/VAP-1 is found in adipocytes, smooth muscle cells, and endothelial cells, and is highly expressed in the lung, aorta, liver, and ileum (Andrés et al, 2001). Membrane-bound SSAO/VAP-1 is proteolytically cleaved by a metalloprotease to release an active, soluble form of the protein (Stolen et al, 2004), which has been shown to be a biomarker of disease progression in patients with liver and kidney fibrosis (Kurkijärvi et al, 1998(Kurkijärvi et al, , 2000(Kurkijärvi et al, , 2001Lin et al, 2008), cancer (Li et al, 2011), cardiovascular disease (Li et al, 2011;Aalto et al, 2012), and metabolic disorders (Boomsma et al, 1999;Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%